Direct selective leaching of chalcopyrite concentrate - Turan, M. D. (Taylor & Francis Ltd, 2014)
The ammonium persulphate (APS) leaching of chalcopyrite concentrate in the presence of ammonium carbonate was studied. The effects of ammonium carbonate concentration, APS concentration, leaching time, leaching temperature, solid/liquid ratio and stirring speed were investigated. Optimum leaching conditions were found as follows: APS concentration is 200 g L-1; ammonium carbonate concentration is 200 g L-1; leaching time is 180 min; leaching temperature is 60 degrees C; solid/liquid ratio is 0.04 g mL(-1); and stirring speed is 400 rev min(-1). Under these conditions, copper extraction yield was obtained at about 72%. Furthermore, iron extraction yield decreased with increasing ammonium carbonate concentration and iron did not pass into solution under this condition. X-ray and SEM analysis also supported these results. It was determined that the copper extraction results were satisfactory by way of all experiments were performed under atmospheric conditions (i.e. low temperature and atmospheric pressure) and achieved selective copper leaching from chalcopyrite concentrate.
Keywords: Copper; Iron; Selective leaching; Dissolution